Psychosocial Determinants Associated with Online Gambling Addiction in Indonesia: A Scoping Review - Nurul Fajriyah Prahastuti; Adinda Istiqomah Azzahra (Journal of Psychological Perspective, 2026)
Online gambling addiction has emerged as a significant public health and social concern in Indonesia, generating complex psychosocial consequences. This scoping review aimed to map the available empirical evidence on psychosocial determinants functioning as risk and protective factors associated with online gambling addiction. The review was conducted in accordance with the PRISMA-ScR guidelines and the Arksey and O'Malley framework (2005). A systematic literature search was performed using the Google Scholar and Garuda databases with the keywords online gambling, gambling addiction, psychosocial factors, psychological factors, social factors, and Indonesia. Article selection was guided by the Population–Concept–Context (PCC) framework. Following the screening and selection process, 14 studies published between 2015 and 2025 met the inclusion criteria and were included in the review. The findings identified five major categories of psychosocial determinants associated with online gambling addiction: psychological, social environmental, technological, economic, and government regulation factors. Psychological and social environmental factors were the most consistently reported determinants, particularly low self-control, sensation seeking, peer influence, and family-related factors. Technological accessibility, financial motivations, and weak regulatory oversight were also identified as contributing factors. This review highlights important evidence gaps and provides insights for the development of preventive interventions and public policies addressing online gambling addiction in Indonesia.